Diabetes mellitus and COVID-19: current state of knowledge - Inga Wasilewska; Jakub Rezmer; Łukasz Świątek (Kazimierz Wielki University, 2022)
Introduction: Diabetes mellitus is a chronic metabolic disease characterized by disturbances in carbohydrate metabolism. Long-term high blood glucose levels can lead to a variety of serious complications and organ failure. Diabetic patients are particularly at risk of the severe course of COVID-19. Objective: The study aimed to investigate the relationship between diabetes and COVID-19. The literature available in the PubMed database was used to carry out a systematic review of the literature. The meta-analyzes from 2021 and 2022 were used for the analysis, with the inclusion of the phrases "DIABETES" and "COVID-19" in the title. A brief description of the state of knowledge: Diabetes does not increase the incidence of COVID-19, but the risk of severe disease is higher in patients with diabetes compared to the non-diabetic population. This is especially true of patients with uncontrolled glycaemia. SARS-CoV-2 disrupts the carbohydrate metabolism, can damage pancreatic beta cells and, in this mechanism, induce diabetes or cause the progression of pre-existing diabetes. There is an increased incidence of COVID-19 complications, including acute respiratory distress syndrome and death in patients with diabetes. Conclusions: Diabetic patients are at a higher risk of the severe course and rapid progression of COVID-19. Important in COVID-19 therapy is glycemic control and monitoring the percentage of glycosylated hemoglobin, CRP and D-dimers. The modification of the current treatment may be necessary. In patients who have undergone COVID-19, attention should be paid to the possibility of induction of diabetes or dysregulation of carbohydrate metabolism in patients suffering from diabetes previously.